Volt-e szerepe a gazdasági tényezőnek az Osztrák-Magyar Monarchia felbomlásában? - Szávai, Ferenc (Közép-Európai Közlemények, 2009)
This paper aims to answer the question whether economic forces played an important role in the Austro-Hungarian Monarchy during the era of Dualism and whether the economic factor contributed to the dissolution of the Austro-Hungarian Monarchy. In 1907, due to conflicts among the parties regarding the common customs area, an arbitral tribunal was set up to solve the difference of opinions. The Dual Monarchy was not only a common customs union but also a tax union. Hungary was greatly indebted for customs abroad and towards Austria. Many Hungarian and Austrian experts favoured economic isolation at the beginning of the 20th century. The permanent discussion about the common customs union and on the quota payment, the difference of opinion, and the economic weariness in the First World War may have played an important role in the dissolution of the Dual Monarchy.